A Local Capacity Market Providing Local and System-wide Flexibility Services - Khajeh, Hosna; Firoozi, Hooman; Hesamzadeh, Mohammad Reza; Laaksonen, Hannu; Shafie-Khah, Miadreza (IEEE, 2021)
A large amount of renewable energy sources and electric vehicles will be integrated into future electricity distribution and transmission systems. New flexibility services from distribution network are needed to manage the related challenges. This paper proposes a local flexible capacity market (LFCM) in the distribution network providing system-wide and local flexibility services for transmission (TSO) and distribution system operators (DSO). The TSO and the DSO play the role of buyers, whereas prosumers connected to the distribution network are the sellers. The LFCM consists of three stages. At the first stage, the offers of flexibility sellers are matched with the bids of flexibility buyers aiming to maximize the social welfare of all participants. At the second stage, the accepted flexible capacities are checked by the DSO not to violate the constraints of the local network. The third stage accepts the offers of the sellers based on the results of the previous stage. The results related to the chosen case study demonstrate that the local flexible resources can help the DSO control the voltage and manage periods of congestion. Besides, the owners of the resources can obtain revenues by selling flexibility services while improving electricity supply reliability.
Keywords: capacity markets; flexibility markets; flexibility services; flexible energy resources; local energy markets; fi=Sähkötekniikka|en=Electrical Engineering|